Wastewater treatment based on remazol blue using DBD plasma reactor under acidic and basic conditions. Issue 1 (January 2021) - Khairunizzahrah, Badzlina; Bismo, Setijo
Abstract: Synthetic dyes are one of the most dangerous components of textile wastewater. Waste that contains various organic compounds, especially synthetic dyes, causes a high Chemical Oxygen Demand (COD) values. Remazol blue is a reactive dye that is widely used for the textile dyeing process. Therefore, water pollution occurs when the dye waste produced from textile activities is discharged into water bodies without prior treatment. In this study, innovation in waste treatment technology was applied in the Dielectric Barrier Discharge (DBD) plasma reactor. DBD are non-thermal plasma reactors designed to degrade organic and inorganic compounds in wastewater through oxidation process. This is carried out by active species, such as ozone (O3), hydrogen peroxide (H2O2) and hydroxyl radical (OH), which are formed in the reactor. The study aims to evaluate the performance of non-thermal DBD plasma reactor in treating wastewater containing one of the textile dyes, namely remazol blue. The results showed that the percentage of degradation achieved was 98.43% within a process time of 120 minutes with a final concentration of 0.75mg/L. Furthermore, it showed that optimum conditions were obtained at pH value of 4, air flow rate of 2.5L/min, liquid flow rate of 50mL/min and a primary Neon sign transformer (NST) voltage of 19kV.